Perlindungan Terhadap Nasabah Dalam Pengamanan Financial Technology Peer To Peer Lending - Surtan Harista Muda Hasibuan; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2021)
Many problem undergone by fintech clients have encouraged the writer interested in doing the research with the title, “Protection for Clients in Securing Financial Technology Peer to Peer Lending. The research problem are as follow : 1)how about the regulation on financial technology of peer to peer lending in Indonesia, 2) whether the legislation in Indonesia related to it has provided security and protection for clients, and 3) whether the regulation on it has provided security and protection for clients. The research employs normative and descriptive analytic method. The legal theories used in the research are the theory of legal protection and the theory of legal certainty